Prevalence and clinical characteristics of obstructive- and central-dominant sleep apnea in candidates of catheter ablation for atrial fibrillation in Japan. (1st June 2018) - Kohno, Takashi; Kimura, Takehiro; Fukunaga, Koichi; Yamasawa, Wakako; Fujisawa, Taishi; Fukuoka, Ryoma; Nakajima, Kazuaki; Kashimura, Shin; Kunitomi, Akira; Katsumata, Yoshinori; Nishiyama, Takahiko; Nishiyama, Nobuhiro; et al.
Abstract: Introduction: We aimed to study the prevalence and types of sleep apnea (SA) as well as their clinical characteristics in atrial fibrillation (AF) ablation candidates in Japan. Methods: Before catheter ablation, 197 consecutive AF patients (age: 60 ± 9 years, body mass index; 25.0 ± 3.0) were evaluated with portable polygraphy. We compared the clinical characteristics, according to the severity of SA as well as its types, as defined by the presence of obstruction and the mixed vs. central apnea indices. Results: The mean apnea–hypopnea index (AHI) was 17.7 ± 11.9, with 135 AF patients having an AHI ≥10 (68.5%). Patients with an AHI ≥10 had a significantly higher body mass index, plasma brain natriuretic peptide (BNP) level, prevalence of hypertension, and larger left atrial size. Among patients with an AHI ≥10, the incidence of obstructive-dominant SA was 60.9% and that of central-dominant SA was 7.6%. The prevalence of hypertension was significantly higher in obstructive-dominant SA patients (obstructive vs. central: 48.3% vs. 20.0%, P = 0.038). The obstructive apnea index correlated with plasma BNP level and age, but the central and mixed apnea indices did not. Conclusions: The prevalence of SA was common in AF ablation candidates, even without an obesity epidemic, and the SA type was predominantly obstructive. Portable polygraphy was useful for detecting undiagnosed SA patients in AF ablation candidates. Highlights: The portable polygraphy was the useful tool for detecting undiagnosed SA patients. AF ablation candidates with SA had a higher body mass index and BNP level. SA type in AF ablation patients was predominantly obstructive and the prevalence of hypertension was significantly higher. Obstructive apnea index correlated with BNP level and age, but central apnea index did not in AF ablation patients.